Chinese migrant workers and occupational injuries: A case study of the manufacturing industry in the Pearl River Delta - Bettina Gransow; Guanghuai Zheng; Apo Leong; Li Ling (United Nations Research Institute for Social Development (UNRISD), 2014)
This paper focuses on the causes and impacts of work-related injuries experienced by migrant workers from manufacturing enterprises in the Pearl River Delta (PRD), a major centre of foreign-invested export industry in China. The paper starts with a brief review of the occupational health and safety legislation in China. The authors analyse a database comprising more than 10,000 cases of injured migrant workers in hospitals in the PRD and in-depth interviews undertaken with injured migrant workers to explore the following questions: how do migrant workers who became victims of occupational accidents describe the conditions, causes and impacts of their work-related injuries? What does this body of knowledge tell us about the gap between the legal situation of occupational health in China and the practical situation of occupational injuries as experienced by migrant workers in the PRD? And how can this knowledge contribute to identifying areas of concern for researchers, policy makers and practitioners? Key findings include the types, frequencies, severity and causes of migrants work-related injuries; the current state of occupational safety and preventive measures; medical treatment and related costs (including a discussion of whether migrants tend to return home after these injuries); and health care services, health insurance and compensation for injured migrant workers. The paper concludes with recommendations for further research as well as for policy and programme interventions to prevent risk and promote protection within the broader context of institutional adaptation in the Chinese health system.
Keywords: 330